The Effects of Various Internal and External Factors on the Movement of the Indonesian Sharia Stock Index on the Indonesia Stock Exchange - Eni Setyowati; Maulidah IH; Daryono Soebagiyo; Rafiq Azzam Al Afif; Annisa Nur Hidayah; Siti Masitoh; Ibrahim Sorie Kamara (Universitas Muhammadiyah Ponorogo, 2024)
This study analyzed several factors that affect the Indonesian Sharia Stock Index. The use of the inflation-currency rate, the availability of money, and the BI rate were all internal factors considered in this study. Meanwhile, the external factors used in this study were international gold and oil prices. The Engle-Granger Error Correction Model was used to analyze time series data in this study. The research used the monthly period started from May 2013 until January 2022. The long-term results of the research variables that could influence the exchange rate, total money supply, world oil prices, and world gold prices were all dependent on the Indonesian Sharia Stock Index. Meanwhile, the factors that influence the short-term movement of the ISSI exchange rates were inflation, and the BI rate variables.